Health Facility Licensing Dispute - Delfina Gusman; Marryo Borry (Unnes Law Journal, 2020)
Clinic is a health service facility that organizes individual health services that provide basic and/or specialist medical services. Primary Clinic (Klinik Pratama) is a Clinic that organizes basic medical services both general and specific. To establish a Klinik Pratama so that it can operate through a series of licensing processes namely Nuisance/Hinder Ordonnantie Permit (HO), Establishment Permit Clinic (IMK) and Clinical Operating Permit (IOK). The results of this process are overlapping or repetitive requirements, making the process ineffective and inefficient. This research is intended to analyze the dispute on health facility licensing in Padang City, West Sumatra. This paper analyzes overlapping of clinical licensing. The main problems that analyzed in this paper concerning to analyze and review clinical licensing, analyze licensing regulations at the Padang City level as a basis for recommendations on simplification, deletion and merging of licenses by the Padang City Government.